Tunisian historical novel - بوعجاجة, سامية (مجلة المخبر أبحاث في اللغة والأدب الجزائري, 2022)
The study sheds light on the Tunisian historical novel, as interest in the novel began early; Specifically since the beginning of the twentieth century, and its topics varied from political, social and historical, the latter took an important place in the novels of Tunisian novelists, so history, with its events, characters, atmosphere, and artistic features, was strongly present. From here, I tried to introduce the historical novel, and to give a brief overview of the Tunisian historical novel, its path and its most important figures, and its most famous novels and their connection to the historical events that marked the history of Tunisia in its different and different phases.